Changes in maternity care policies and practices that support breastfeeding as measured by the Ten Steps to Successful Breastfeeding - United States, 2018-2022 - Kristin J. Marks; Lucas Gosdin; Lauren E. O'Connor; Heather C. Hamner; Daurice A. Grossniklaus (BMC, 2024)
Abstract Background Experiences during the birth hospitalization affect a family's ability to establish and maintain breastfeeding. The Ten Steps to Successful Breastfeeding (Ten Steps) describe evidence-based hospital policies and practices shown to improve breastfeeding outcomes. We aim to describe hospitals' implementation of the Ten Steps, changes over time, and hospitals' implementation of a majority (≥ 6) of the Ten Steps by hospital characteristics and state. Methods The biennial Maternity Practices in Infant Nutrition and Care (mPINC) survey assesses all hospitals in the United States (including the District of Columbia and territories) that routinely provide maternity care services. We analyzed data from 2018, 2020, and 2022 survey cycles to describe trends in the prevalence of hospitals implementing maternity care policies and practices that are consistent with the Ten Steps. Differences were calculated using the absolute difference in percentage-points between 2018 and 2022. Results Between 2018 and 2022, the percentage of hospitals that implemented Step 2: Staff Competency and Step 5: Support Mothers with Breastfeeding increased 12 and 8 percentage points, respectively. The percentage of hospitals that implemented Step 6: Exclusive Breastfeeding Among Breastfed Infants was 7 percentage points lower in 2022 than 2018. Implementation of the remaining seven steps did not change by more than 5 percentage points in either direction between 2018 and 2022. Nationally, the percentage of hospitals that implemented ≥ 6 of the Ten Steps increased from 44.0% in 2018 to 51.1% in 2022. Differences were seen when comparing implementation of ≥ 6 of the Ten Steps by hospital characteristics including state, hospital size, and highest level of neonatal care offered. Conclusions Nationally, maternity care policies and practices supportive of breastfeeding continued to improve; however, certain practices lost progress. Differences in implementation of the Ten Steps were observed across states and by certain hospital characteristics, suggesting more work is needed to ensure all people receive optimal breastfeeding support during their delivery hospitalization.